Blood Pressure Effects of Canagliflozin and Clinical Outcomes in Type 2 Diabetes and Chronic Kidney Disease: Insights From the CREDENCE Trial. Issue 18 (8th February 2021) - Ye, Nan; Jardine, Meg J.; Oshima, Megumi; Hockham, Carinna; Heerspink, Hiddo J.L.; Agarwal, Rajiv; Bakris, George; Schutte, Aletta E.; Arnott, Clare; Chang, Tara I.; Górriz, Jose L.; Cannon, Christopher P.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: People with type 2 diabetes and chronic kidney disease experience a high burden of hypertension, but the magnitude and consistency of blood pressure (BP) lowering with canagliflozin in this population are uncertain. Whether the effects of canagliflozin on kidney and cardiovascular outcomes vary by baseline BP or BP-lowering therapy is also unknown. Methods: The CREDENCE trial (Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation) randomized people with type 2 diabetes and chronic kidney disease to canagliflozin or placebo. In a post hoc analysis, we investigated the effect of canagliflozin on systolic BP across subgroups defined by baseline systolic BP, number of BP-lowering drug classes, and history of apparent treatment-resistant hypertension (BP ≥130/80 mm Hg while receiving ≥3 classes of BP-lowering drugs, including a diuretic). We also assessed whether effects on clinical outcomes differed across these subgroups. Results: The trial included 4401 participants, of whom 3361 (76.4%) had baseline systolic BP ≥130 mm Hg, and 1371 (31.2%) had resistant hypertension. By week 3, canagliflozin reduced systolic BP by 3.50 mm Hg (95% CI, –4.27 to –2.72), an effect maintained over the duration of the trial, with similar reductions across BP and BP-lowering therapy subgroups (all P interaction ≥0.05). Canagliflozin also reduced the need for initiation of additional BP-lowering agents during the trial (hazard ratio, 0.68 [95% CI, 0.61–0.75]). The effect of canagliflozin on kidney failure, doubling of serum creatinine, or death caused by kidney or cardiovascular disease (hazard ratio, 0.70 [95% CI, 0.59–0.82]) was consistent across BP and BP-lowering therapy subgroups (all P interaction ≥0.35), as were effects on other key kidney, cardiovascular, and safety outcomes. Conclusions: In people with type 2 diabetes and chronic kidney disease, canagliflozin lowers systolic BP across all BP-defined subgroups and reduces the need for additional BP-lowering agents. These findings support use of canagliflozin for end-organ protection and as an adjunct BP-lowering therapy in people with chronic kidney disease. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02065791.